Observer-Based Event-Triggered Fuzzy Integral Sliding Mode Control for Hindmarsh Rose Neuronal Model Via T-S Fuzzy systems - Nirvin, P.; Rakkiyappan, R. (Journal of Applied Nonlinear Dynamics, 2026)
The problem of stability for nonlinear Hindmarsh-Rose (H-R) neuron model with event-triggered fuzzy Integral Sliding Mode Control (ISMC) design is investigated via Takagi-Sugeno (T-S) fuzzy systems. The Event-triggered Communication (ETC) scheme is introduced with a triggered condition of the sampling instant to determine whether the current sampled signal should be transmitted or not. {In order to send and receive the delay measurements for updating the control, the event triggered zero-order-holder (ZOH) is employed. Also, a note observer is designed for the estimation of system state and for the facilitation of the sliding surface design.} Then by analyzing the measured output and observer output, a novel law is presented. Further the stability criterion and the stabilization conditions are estimated based on Lyapunov-Krasovskii functional (LKF) to ensure the asymptotically stability for the considered system. Finally, a numerical example is presented to demonstrate the feasibility of the proposed design scheme.